Risks and governance of heavy metals in European soil applied phosphate fertilizers - Lian-kai Zhang; Xiang Liu; Ya-jie Sun; Bernd G. Lottermoser; Roland Bol; Heike Windmann; Silvia H. Haneklaus; Ewald Schnug (China Geology)
ABSTRACT: Phosphorus (P) poses a global challenge to the environment and human health due to its natural association with heavy metals. Sustainable use of P is crucial to ensure food security for future generations. An analysis of the 150 phosphate fertilizers stored at the Institute for Crop and Soil Science in Germany has been conducted, supplemented by previously published data. The elements Cd, Bi, U, Cr, Zn, Tl, As, B, Sb, Ni, and Se are found in higher concentrations in sedimentary derived phosphates compared to igneous derived phosphates. Mineral fertilizers contain more than ten times the amount of U, Cd, B, and As compared to farmyard manure. Principal component analyses (PCA) indicate that U, Cd, Be, and Cr are primarily present in sedimentary derived phosphates and their concentrations are 2 to 10 times higher than those in igneous derived phosphates. Regarding heavy metal contamination, over 1000 potential combinations were identified; 36% of these were significant but weak (> 0.1). It is estimated that approximately 707 t of uranium enter farmland annually through the application of mineral phosphate fertilizers in European countries. This contribution addresses environmental issues related to the utilization of rock phosphate as well as alternative production methods for cleaner and safer phosphate fertilizers while presenting a roadmap with measures for mitigation.